Evaluation of ELISA-Based Antioxidant Biomarkers and Hematological Pa rameters as Diagnostic Indicators of Fasciolosis in Calves (Indian Journal of Animal Production and Management, 2026)
Background: Fasciolosis is a prevalent parasitic diseasethat affects mammals  worldwide. This disease is associated with global veterinary and economic  importance in the livestock breeding and production systems, particularly  cattle. In infected animals, fasciolosis may induce significant disturbances in the  hematological profile and oxidative stress biomarkers. Aim: This study aimed to  evaluate selected oxidative stress biomarkers (by using bovine-specific ELISA kits  in place of the traditional methods) and hematological changes in calves naturally  infected with fasciolosis and to assess their possible role as supportive diagnostic  indicators of the disease. Methods: This study involved a total of 89 male calves  (20–24 months old). The animals included in this study were randomly selected  from those presented for slaughter throughout the study period. Post-mortem  macroscopic examination of the liver and bile ducts, along with microscopic  identification of trematodes based on morphological features, was used to confirm  infection. Blood samples were collected, and serum was separated for biochemical  analysis. Oxidative stress biomarkers were assessed using bovine-specific ELISA  kits, and hematological parameters were measured using an automated complete  blood count (CBC) analyzer. Results: Infected calves showed a highly significant  reduction in antioxidant parameters compared with controls. Mean serum SOD,  CAT, and GSH levels in infected animals (574.88 ± 26.71 pg/mL, 0.96 ± 0.13 ng/ mL, and 6.97 ± 0.58 ng/mL, respectively) were significantly lower in infected  animals versus controls (940.80 ± 42.94 pg/mL, 3.43 ± 0.38 ng/mL, 18.54 ± 0.24  ng/mL, respectively). Conversely, MDA levels (155.99 ± 15.09 ng/mL) were  markedly elevated in the infected group compared to controls (55.78 ± 3.76 ng/ mL).The hematological analysis revealed significant alterations in the infected  group compared to the control group. The mean RBC count in infected animals  (7.45 ± 0.51 × 10¹²/L) was significantly lower than that in the control group (10.0  ± 0.55 × 10¹²/L). Similarly, hemoglobin (HGB) levels were markedly decreased in  infected animals (8.80 ± 0.92 g/dL) versus controls (14.0 ± 0.72 g/dL). Hematocrit  (HCT) values also showed a significant reduction in infected animals (26.6 ±  3.0%) compared to controls (42.1 ± 2.2%). In addition, mean corpuscular volume  (MCV) and mean corpuscular hemoglobin (MCH) were significantly lower in the  infected group (35.7 ± 3.4 fL and 11.8 ± 1.5 pg, respectively)  than in the control group (42.1 ± 3.1 fL and 14.0 ± 1.1 pg,  respectively).In contrast, no significant difference was  observed in mean corpuscular hemoglobin concentration  (MCHC) between the infected (33.0 ± 1.9 g/dL) and control  groups (33.2 ± 1.4 g/dL). Conclusion: Fasciolosis has a  notable impact on both biochemical and hematological  profiles in calves; such clinicopathological alterations may  serve as valuable supportive markers for determining the  physiological consequences of infection and may aid in early  diagnosis, assessment of disease severity, and monitoring  the progression of infection. Additional research is needed  to determine the effect of preventing or promptly correcting  these alterations in accelerating recovery and improving the  overall health condition of affected animals.
Keywords: Fasciolosis,FasciolaSpp., oxidative stress, hematological parameters, ELISA.